Pathologic complete responses and overall survival after neoadjuvant chemotherapy for muscle-invasive bladder cancer: Analyzing the impact of race. Issue 28 (1st October 2022) - Roy, Arya Mariam; Jiang, Changchuan; Perimbeti, Stuthi; Jatwani, Karan; Chatta, Gurkamal S.; Gopalakrishnan, Dharmesh
Abstract : 146 Background: Neoadjuvant chemotherapy (NAC) has been demonstrated to improve overall survival (OS) after radical cystectomy (RC) in patients with muscle-invasive bladder cancer (MIBC). We compared pathologic complete response (PCR) rates and OS after NAC between African American (AA) and Caucasian patients with MIBC. Methods: We queried the National Cancer Database for Caucasian and AA patients with localized MIBC (cT2-T4aN0M0) with urothelial histology who received NAC + RC between 2007 and 2018. We excluded patients who belonged to other races, had nodal or distant metastases, non-urothelial histology, did not receive NAC, or had missing pathological data. Logistic regression was used to analyze PCR and residual disease (RD) and Cox proportional hazards regression to analyze OS, with adjustment for age at diagnosis, race, stage, grade, insurance, treatments received, and comorbidities. STATA/IC 16.0 was used for analysis and a two-sided p-value < 0.05 was considered significant. Results: A total of 7008 Caucasians and 424 AAs with MIBC were identified. 75.6% were males and 24.4% were females. Among those who received NAC, only 12.6% (n = 933) attained PCR and 87.4% (n = 6499) had RD. Among Caucasians, 12.76% (n = 894) attained PCR and 87.24% (n = 6114) had RD. Among AAs, 9.2 % (n = 39) had PCR and 90.8% (n = 385) had RD. AA had more likelihood of attaining PCR when compared to Caucasians, but was not statistically significant (OR = 1.35, 95% CI = 0.966 – 1.90, p = 0.078). The median OS of patients with PCR and RD were 144 and 47 months respectively. Patients who had RD had significantly higher mortality risk when compared to those who attained PCR (HR = 3.67, 95% CI = 3.14-4.29, p < 0.01). In the PCR group and RD groups, AA vs Caucasian race was not associated with a statistically significant mortality benefit in univariate or multivariate analysis. Within PCR and RD groups, AAs were found to have mortality risk compared to Caucasians (PCR group: HR = 1.53, 95% CI = 0.2-1.43, p = 0.21 and RD group: HR = 1.07, 95% CI = 0.93- 1.2, p = 0.34). Conclusions: PCR with NAC in localized MIBC was associated with significantly improved overall survival. AA or Caucasian race was not independently predictive of PCR or OS after NAC in MIBC.